2007
DOI: 10.1136/ard.2007.071910
|View full text |Cite
|
Sign up to set email alerts
|

Baseline serum RANKL levels may serve to predict remission in rheumatoid arthritis patients treated with TNF antagonists

Abstract: These data suggest that in patients receiving a-TNF treatment, lower serum levels of RANKL and RANKL/OPG ratio may serve to predict remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
9
32
0
Order By: Relevance
“…Further research showed that 35 consecutive patients with RA with low serum COMP levels had improved clinical responses to adalimumab 61. Moreover, 75 patients with longstanding RA treated with adalimumab or infliximab who achieved remission (DAS28 <2.6) had lower receptor activator for nuclear factor-κB ligand (RANKL) and RANKL:osteoprotegerin ratio at baseline 62. The balance between osteoprotegerin and RANKL is a fundamental factor in controlling bone resorption and can be influenced by several hormones and cytokines, including TNF.…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Further research showed that 35 consecutive patients with RA with low serum COMP levels had improved clinical responses to adalimumab 61. Moreover, 75 patients with longstanding RA treated with adalimumab or infliximab who achieved remission (DAS28 <2.6) had lower receptor activator for nuclear factor-κB ligand (RANKL) and RANKL:osteoprotegerin ratio at baseline 62. The balance between osteoprotegerin and RANKL is a fundamental factor in controlling bone resorption and can be influenced by several hormones and cytokines, including TNF.…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…b Number of RANKL-positive neutrophils (%) in joint extracts from healthy and CIOA mice. Data represent mean ± SD of 6 mice/group and were obtained within Ly-6/CD11b-positive neutrophils; Student's t-test; *P \ 0.05, **P \ 0.01, ***P \ 0.001 therapy [26]. In OA patients, serum concentrations of sRANKL correlated significantly with sRANKL level in the synovial fluid, while for OPG such relation has not been found [27].…”
Section: Discussionmentioning
confidence: 94%
“…Collagenase-induced osteoarthritis (CIOA) Experimental model of OA was induced according the method of Blom et al [26]. Mice received two intraarticular injections (i.a.)…”
Section: Methodsmentioning
confidence: 99%
“…Mathematical models have been extensively and successfully used in different medical field to predict clinical response to different drugs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%